2013
DOI: 10.1507/endocrj.ej13-0198
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sitagliptin as add-on therapy on glycemic control and blood glucose fluctuation in Japanese type 2 diabetes subjects ongoing with multiple daily insulin injections therapy

Abstract: To assess the efficacy and safety of adding sitagliptin, an oral dipeptidyl peptidase-4 inhibitor, in subjects with type 2 diabetes inadequately controlled with multiple daily insulin injections therapy (MDI). HbA1c, 1,5-anhydroglucitol (1,5-AG), body mass index (BMI), insulin doses, six-point self-measured plasma glucose (SMPG) profiles were assessed before, after 12 weeks, and after 24 weeks of MDI with 50 mg/day of sitagliptin in 40 subjects with type 2 diabetes. Safety endpoints included hypoglycemia and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
3
19
1
1
Order By: Relevance
“…Sitagliptin, a dipeptidyl peptidase 4 (DPP-4) inhibitor, increases insulin secretion and suppresses glucagon release by protecting the degradation of incretins without increased risk of hypoglycemia and clinically relevant weight gain (8,9). Furthermore, the addition of DPP-4 inhibitors to ongoing insulin therapy was reported to have specific advantages in reducing the frequency of hypoglycemia and weight gain, in addition to the expected benefits associated with glycemic control and limiting insulin dose (10)(11)(12).…”
mentioning
confidence: 99%
“…Sitagliptin, a dipeptidyl peptidase 4 (DPP-4) inhibitor, increases insulin secretion and suppresses glucagon release by protecting the degradation of incretins without increased risk of hypoglycemia and clinically relevant weight gain (8,9). Furthermore, the addition of DPP-4 inhibitors to ongoing insulin therapy was reported to have specific advantages in reducing the frequency of hypoglycemia and weight gain, in addition to the expected benefits associated with glycemic control and limiting insulin dose (10)(11)(12).…”
mentioning
confidence: 99%
“…This meal consists of 5 crackers, a cup of pudding, and a cup of chicken cream stew and contains a total energy of 450 kcal with 51.4% from carbohydrates, 33.3% ing glucagon secretion [9][10][11][12]. Although these drugs were also demonstrated to ameliorate poor blood glucose control in insulin-treated type 2 diabetes patients [13][14][15][16], few studies have reported on blood glucose lowering mechanisms, especially in East Asian populations. In patients on insulin monotherapy, peripheral blood insulin levels are sufficient.…”
Section: Meal Tolerance Testmentioning
confidence: 99%
“…This discrepancy may be attributed to the different subjects as well as different background treatments. For example, it is reported DPP-4 inhibitors are more efficacious in Asian [20].…”
Section: Resultsmentioning
confidence: 99%